Medium-Chain Fatty Acids Improve Cognitive Function in Intensively Treated Type 1 Diabetic Patients and Support In Vitro Synaptic Transmission During Acute Hypoglycemia - Page, Kathleen A.; Williamson, Anne; Yu, Namyi; McNay, Ewan C.; Dzuira, James; McCrimmon, Rory J.; Sherwin, Robert S. (Diabetes (New York, N.Y.), 2009)
Medium-Chain Fatty Acids Improve Cognitive Function in Intensively Treated Type 1 Diabetic Patients and Support In Vitro Synaptic Transmission During Acute Hypoglycemia Kathleen A. Page 1 , Anne Williamson 2 , Namyi Yu 3 , Ewan C. McNay 4 , James Dzuira 5 , Rory J. McCrimmon 1 and Robert S. Sherwin 1 1 Section of Endocrinology, Yale School of Medicine, New Haven, Connecticut; 2 Department of Neurosurgery, Yale School of Medicine, New Haven, Connecticut; 3 Winthrop University Hospital, Long Island, New York; 4 Department of Psychology, State University of New York, University at Albany, Albany, New York; and 5 Yale Center for Clinical Investigation, New Haven, Connecticut. Corresponding author: Kathleen A. Page, kathleen.pageatyale.edu . Abstract OBJECTIVE We examined whether ingestion of medium-chain triglycerides could improve cognition during hypoglycemia in subjects with intensively treated type 1 diabetes and assessed potential underlying mechanisms by testing the effect of β-hydroxybutyrate and octanoate on rat hippocampal synaptic transmission during exposure to low glucose. RESEARCH DESIGN AND METHODS A total of 11 intensively treated type 1 diabetic subjects participated in stepped hyperinsulinemic- (2 mU · kg −1 · min −1 ) euglycemic- (glucose ∼5.5 mmol/l) hypoglycemic (glucose ∼2.8 mmol/l) clamp studies. During two separate sessions, they randomly received either medium-chain triglycerides or placebo drinks and performed a battery of cognitive tests. In vitro rat hippocampal slice preparations were used to assess the ability of β-hydroxybutyrate and octanoate to support neuronal activity when glucose levels are reduced. RESULTS Hypoglycemia impaired cognitive performance in tests of verbal memory, digit symbol coding, digit span backwards, and map searching. Ingestion of medium-chain triglycerides reversed these effects. Medium-chain triglycerides also produced higher free fatty acids and β-hydroxybutyrate levels compared with placebo. However, the increase in catecholamines and symptoms during hypoglycemia was not altered. In hippocampal slices β-hydroxybutyrate supported synaptic transmission under low-glucose conditions, whereas octanoate could not. Nevertheless, octanoate improved the rate of recovery of synaptic function upon restoration of control glucose concentrations. CONCLUSIONS Medium-chain triglyceride ingestion improves cognition without adversely affecting adrenergic or symptomatic responses to hypoglycemia in intensively treated type 1 diabetic subjects. Medium-chain triglycerides offer the therapeutic advantage of preserving brain function under hypoglycemic conditions without causing deleterious hyperglycemia. Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Received November 10, 2008. Accepted February 4, 2009. Readers may use this article as long as the work is properly cited, the use is educational and not for profit, and the work is not altered. See http://creativecommons.org/licenses/by-nc-nd/3.0/ for details. © 2009 by the American Diabetes Association.